"Gaus's choice": The Open Society as an ideal. (March 2018) - Singer, Abraham
Gaus has recently offered a novel argument for an open society, connecting it to recent methodological debates regarding ideal and non-ideal theory. The argument, briefly put, is that political philosophies based upon the search for an ideal to anchor their critical and prescriptive ambitions, so-called "ideal theories, " are bound to fail. The best possible case for doing ideal theory should lead us to recognize that such endeavors are conceptually incoherent or lead to morally perverse outcomes. Consequently, the best way to approximate a knowledge of the optimal institutional state of affairs is to organize institutions around the goal of maximizing perspectival diversity, what Gaus calls the "Open Society, " not according to an ideal blueprint. I argue that precisely because ideal theory has the problems that Gaus skillfully illuminates, we should be skeptical about the picture he paints of the Open Society.